(untitled) (Communications in Computational Physics, 2018)
The full torus electromagnetic gyrokinetic particle simulations using the hybrid model with kinetic electrons in the presence of magnetic shear is presented. The fluid-kinetic electron hybrid model employed in this paper improves numerical properties by removing the tearing mode, meanwhile, preserves both linear and nonlinear wave-particle resonances of electrons with Alfven wave and ion acoustic wave.